Perception of generating extra income among public servant in Hospital Likas and IPK Kepayan (PDRM) / Anis Zahraa Ahmadi and Norzieyati Dzulkiflie - Ahmadi, Anis Zahraa; Dzulkiflie, Norzieyati (2016)
The tem1 generating extra income activities are popular among public servant. This means that they generate extra income at the same time they have their actual job. Some opinions assume that generating extra income activities will affect the personal life of an individual. The personal life refers to family relationship, work performance and health. The objectives of this research are to study the personal life among public servant, to measure the perception towards generating extra income activities among public servant, and to study the association between the personal life and perceptions of generating extra income activities.